2020
DOI: 10.3390/horticulturae6040083
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Circular Economy Concept in Greenhouse Hydroponics for Ultimate Use of Water and Nutrients

Abstract: The circular economy in agriculture aims to reduce waste while also making best use of residues by using economically viable processes and procedures to increase their value. In this study a two-level cascade cultivation system was set up under greenhouse conditions. The research was focused on the identification of crop species as secondary crops and the development/iterative optimization of cultivation practices. For this purpose, different crop-combinations with a primary and different secondary crops were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 19 publications
2
24
0
3
Order By: Relevance
“…Similar growth restrictions were also recorded in the T5 plants in the first experiment (Figures 1 and 2). Elvanidi et al (2020) [5] reported similar reductions of basil grown in cascade hydroponics in which basil received only 40% of cucumber drainage complemented with typical irrigation water. The total amino acid content of basil that received the drainage solution from cucumber (hereinafter referred to as "treated plants") displayed a trend for higher values compared to the control only at the final harvest (Figure 6).…”
Section: Is Basil Suitable As a Secondary Crop In A Cascade Hydroponics System?mentioning
confidence: 77%
See 4 more Smart Citations
“…Similar growth restrictions were also recorded in the T5 plants in the first experiment (Figures 1 and 2). Elvanidi et al (2020) [5] reported similar reductions of basil grown in cascade hydroponics in which basil received only 40% of cucumber drainage complemented with typical irrigation water. The total amino acid content of basil that received the drainage solution from cucumber (hereinafter referred to as "treated plants") displayed a trend for higher values compared to the control only at the final harvest (Figure 6).…”
Section: Is Basil Suitable As a Secondary Crop In A Cascade Hydroponics System?mentioning
confidence: 77%
“…Similar growth restrictions were also recorded in the T5 plants in the first experiment (Figures 1 and 2). Elvanidi et al (2020) [5] reported similar reductions of basil grown in cascade hydroponics in which basil received only 40% of cucumber drainage complemented with typical irrigation water.…”
Section: Exploration Of Salinity-tolerance Thresholds Of Basilmentioning
confidence: 92%
See 3 more Smart Citations